Antoni Wędrychowski – przemysłowiec z pomysłem. Przyczynek do historii Suchedniowa na przełomie XIX i XX w. - Włodarczyk-Mazurek, Agnieszka (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Suchedniów is a small town situated in the Kamienna River valley on the contemporary freeway built between Cracow and Warsaw, and in the centre of the historical Old-Polish Industrial Region. At the end of 19th century Antoni Wędrychowski, a young man inured to labour, an industrialist descending from a landowning family, began his activities there. Thanks to the support of his godfather, he got a job in the Mining and Smelting Plant in Stąporków and Siel, and then he was appointed a mine master of clay mine in Bliżyn. At the beginning of the 1890s he founded an iron mine and built a narrow gauge railway connecting furnaces and roasters with the railway station in Suchedniów. When exploiting the ore was no longer profitable, he begun extracting red and white sandstone. On an industrial and farming exhibition in Częstochowa in 1909 the products from Wędrychowski’s company received a “big silver medal” for introducing sandstone into industry (i.e. bathtubs for etching steel pipes). Simultaneously with extracting the stone, he opened a fireproof white clay mine, and on the basis of this raw material he established a ceramics plant after World War I. It remained in the hands of the Wędrychowski family barely till 1929 when it was sold to the “Marywil” company from Radom, manufacturing at that time stoneware and chamotte products.